Thinking Past Henri Lefebvre: Introducing "The Theory of Ground Rent and Rural Sociology". Issue 1 (15th July 2015) - Elden, Stuart; Morton, Adam David
Abstract: This introduction to the translation of Henri Lefebvre's 1956 essay "The theory of ground rent and rural Sociology" moves through three stages. First, it suggests that Anglophone appropriations of Lefebvre have tended to focus too much on his urban writings, at the expense of understanding his early work on rural sociology, and failing to recognise how his urban focus emerged as a result of his interest in rural–urban transformation. Second, it provides a summary of his wider work on rural questions, including his unfinished work on a major treatise of rural sociology; and outlines the key themes of the present essay in relation to these other projects. Third, it connects Lefebvre's issues to wider debates in political economy and geography about aspects of the rural, land and ground rent, not least including the work of Antonio Gramsci and José Carlos Mariátegui.